SCIENTIFIC THINKING: A BASIS OF ORGANIZATION FOR PHYSICAL SCIENCE LABORATORY PROGRAMS IN COLLEGE GENERAL EDUCATION. - Perlman, James S. (Science Education, 1955)
The article examines the use of scientific thinking as basis of organization for physical science laboratory programs in college general education in San Francisco, California. The study emphasizes historical and contemporary problem-solving treatment of the physical science laboratory period for college general education. Science laboratory period for general education purposes lie in the opportunities it provides for first hand material, first hand evidence and first hand experience. Laboratory period is devoted to conscious scientific problem-solving aims, procedures and materials in order to achieve scientific problem-solving approaches, attitudes and outcomes.